2022
DOI: 10.3390/curroncol29060323
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Healthcare Professionals’ Mental Health during the COVID-19 Pandemic

Abstract: The paper begins by reviewing the literature on oncology healthcare professionals’ (HCP) mental health. We summarize and present the current data on HCP mental health in order to understand the baseline state of oncology HCPs’ mental health status prior to the COVID-19 pandemic. At each juncture, we will discuss the implications of these mental health variables on the personal lives of HCPs, the healthcare system, and patient care. We follow by reviewing the literature on these parameters during the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 89 publications
0
18
0
3
Order By: Relevance
“…Around 60% of participants felt supported by their friends and family, and their workplace, during COVID (Banerjee et al, 2021). Similarly, a UK study by Ferry et al (2021) found that HCPs who were younger, female, had been redeployed from their usual role and worked in areas dedicated to COVID‐19 patients had increased likelihood of moderate to severe burnout, with complementary findings reported by a recent literature review focused on oncology professionals' mental health during the pandemic (Granek & Nakash, 2022). Increased risk of burnout and psychological distress is perhaps unsurprising when considering the additional stressors that oncology HCPs faced during the pandemic; in addition to workplace‐level challenges (e.g.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Around 60% of participants felt supported by their friends and family, and their workplace, during COVID (Banerjee et al, 2021). Similarly, a UK study by Ferry et al (2021) found that HCPs who were younger, female, had been redeployed from their usual role and worked in areas dedicated to COVID‐19 patients had increased likelihood of moderate to severe burnout, with complementary findings reported by a recent literature review focused on oncology professionals' mental health during the pandemic (Granek & Nakash, 2022). Increased risk of burnout and psychological distress is perhaps unsurprising when considering the additional stressors that oncology HCPs faced during the pandemic; in addition to workplace‐level challenges (e.g.…”
Section: Introductionmentioning
confidence: 77%
“…reduced in‐person contact with patients; redeployment; increased patient distress and complexity in needs), oncology HCPs report experiencing personal‐level difficulties such as worry about risk to family and friends, concern regarding personal health, financial pressures (e.g. due to concerns about job insecurity and career progression/development) and difficulties balancing work with family life, for example home schooling (Downey & Ash‐Lee, 2021; Granek & Nakash, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of healthcare professionals (HCPs) to manage and mitigate the adverse effects of facing difficult situations is essential to maintaining quality care for people living with and beyond cancer (PLWBC). Adversity arises from daily exposure to the suffering of patients, heavy workload and time pressures, workforce shortages, and administrative burdens [1]. The lengthy and profound disruption produced by the COVID-19 pandemic compounded a longstanding cancer crisis [2], aggravating scarcities of material and human resources and the siloed functioning of cancer care provision [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial clinicians working in oncology settings (e.g., social workers, psychologists) show a similarly high risk of burnout [10]. Since 2020, there has been an exponential increase in studies on stress at work among oncology HCPs, responding to the exacerbation of work-related stress syndromes caused by the COVID-19 pandemic [1,3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation